MC, Malandra, Funkstar: os trânsitos de Anitta entre pop e funk na construção do funk brasileiro contemporâneo (2012-2024) - CAMPOS, Alexandre Duarte (Universidade Federal do Oeste do Pará, 2026)
The history of contemporary Brazilian funk can be analyzed through the career trajectory of the Brazilian artist Anitta. Accordingly, the primary objective of this study was to analyze Anitta’s musical and aesthetic contributions to the development of contemporary Brazilian funk between 2012 and 2024. The methodology employed was documentary and bibliographic research, utilizing three groups of sources spanning the 2012–2024 period: a) Group 1: Anitta’s artistic output—albums, singles, music videos, and projects; b) Group 2: interviews in which the artist discusses her own work and her presence within the funk genre; and c) Group 3: critical writings regarding Anitta’s work. To understand the development of contemporary Brazilian funk through the lens of Anitta’s career, the study drew upon the concept of the “coloniality of power and being” to examine the stigmatization and criminalization of funk as a form of Black culture. The research findings indicate that, since the start of her career in 2012, the Brazilian singer has contributed significantly to Brazilian popular music; her work has brought musical and aesthetic innovations to the pop/funk sector, both domestically and through the export of her music to the international stage.
Keywords: Funk brasileiro - História e crítica; Música popular - Brasil; Anitta (Cantora) - Crítica e interpretação; Música e sociedade; Colonialidade; CNPQ:: CIÊNCIAS HUMANAS